Distribution of Blood Groups in Patients with Atopic Dermatitis: A Retrospective Case-Control Study - Çelik, Candan; Çelik, Mehmet Semih (The European Research Journal, 2026)
Objectives: Atopic dermatitis is a chronic inflammatory skin condition with a multifactorial etiology involving genetic, environmental, and immunologic influences. Although several mechanisms have been proposed, the potential association between ABO/Rh blood groups and the risk of developing atopic dermatitis is still uncertain. The present study sought to investigate the distribution of ABO and Rh blood groups in individuals with atopic dermatitis compared with healthy, age- and sex-matched controls. Methods: A retrospective analysis was performed covering a 10-year interval (2014–2024). The study included 3,470 patients diagnosed with atopic dermatitis and 7,449 matched controls, yielding a total sample of 10,919 individuals. Demographic data and blood group characteristics (ABO and Rh typing) were collected and evaluated. Results: The O Rh– phenotype was observed significantly more often in patients with atopic dermatitis than in controls (5.2% vs. 3.5%; OR=1.52, 95% CI: 1.25–1.85; P